Kajian Roland Barthes Terhadap Makna Dalam Video Klip BTS “Yet to Come” - Salsabila, Jihan; Kholik, Kholik (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to uncover the layers of meaning contained in the music video